FIRM VALUE ANALYSIS IN INDONESIA MANUFACTURING COMPANIES - Falisca Falisca; Maria Stefani Osesoga (Ultimaccounting Jurnal Ilmu Akuntansi, 2023)
Abstract - The objective of this research is to obtain empirical evidence regarding the effect of firm size, dividend policy, profitability, and leverage on firm value. Firm value is very important because it reflects the company's performance which can affect investors' and creditors’ consideration for economic decision-making. The object of this study is manufacturing companies listed on Indonesia Stock Exchange for the period 2017-2020. The sample taken for this study was 24 companies based on the purposive sampling method and data was analyzed by using the multiple linear regression method. The results of this research are firm size, dividend policy, and profitability have a positive significant effect on firm value, while leverage has no effect on firm value. This study proves that asset efficiency has a major influence in determining firm value of manufacturing companies. Thus, companies must increase the effectiveness of assets in their operating and investment activities. Keywords: Dividend Policy; Firm Size, Firm Value, Leverage, Profitability